(untitled) (Bioresearch Communications, 2026)
Background and aim: Mitochondria are crucial for cellular energy production and apoptosis. It plays a crucial part in the development of cancer. This pilot study looked at mitochondrial ATP6 polymorphisms as a potential preliminary indicator for breast cancer in Bangladeshi women. Materials and Methods: The MT-ATP6 gene of mitochondrial DNA was sequenced from 13 breast cancer tissue samples. Sequencing data were compared with the Revised Cambridge Reference Sequence (rCRS) to detect polymorphisms. Blood samples from 33 healthy women were also analyzed as controls to account for variations. Results: A total of five mutations were identified by analysing the sequences of patient samples. Three of the five mutations (m.8701A>G, m.8860A>G, and m.9094C>T) were nonsynonymous, and two (m.8772T>C and 8790G>A) were synonymous. The m.8701A>G and m.8860A>G mutations were detected in both cancer patients and healthy controls and no statistical significance was calculated due to the small sample size. The m.8701A>G mutation was observed in 4 out of 13 (30.77%) cancer patients, and the m.8860A>G mutation was observed in 11 out of 13 (84.61%) cancer patients. Focus was placed on the m.9094C>T mutation, which was observed in two out of thirteen (15.38%) breast cancer patients, and was entirely absent in the control group (0/33). This mutation in Bangladeshi women results in a Leucine (L) to Phenylalanine (F) substitution at codon 120. According to PolyPhen-2 analysis, this variant is "possibly damaging," with a score of 0.855. Structural analysis using the HOPE tool revealed alterations in protein structure, while DynaMut confirmed impacts on structural features. These findings suggest that the m.9094C>T mutation may be indirectly linked to an increased risk of breast cancer. Conclusion: The detection of m.9094C>T exclusively in two patient samples, coupled with its predicted pathogenicity, identifies this variant as an interesting candidate for future, large-scale investigation. These preliminary findings do not establish a definitive association or heritability but suggest that variants in the MT-ATP6 gene warrant further functional and epidemiological investigation as potential susceptibility factors for breast cancer. Bioresearch Commu. 12(1): 1972-1980, 2026 (January)